Towards understanding the differences in irradiation effects of He, Ne and Ar plasma by investigating the physical origin of their clustering in tungsten. (28th July 2016) - Kong, Xiang-Shan; You, Yu-wei; Li, Xiang-yan; Wu, Xuebang; Liu, C.S.; Chen, Jun-Ling; Luo, G.-N.
Abstract: While inert gas seeding to improve energy confinement has been successfully applied in many tokamak experiments, questions remain as to the irradiation effects of inert gases on tungsten. In this paper, we have systematically investigated the clustering behaviors of the inert gas atoms He, Ne and Ar in plasma-facing tungsten using first-principles calculations. Small interstitial clusters, He m, Ne m, and Ar m, can form due to the attraction between the atoms and tend to expand along the (1 1 0) planes. The inert gas clusters induce strong lattice distortions and so it is energetically favorable for a self-interstitial atom to be emitted from the clusters when the numbers of atoms are above six, three, three for He m, Ne m, and Ar m respectively. The clustering behaviors can be well explained by the intrinsic repulsive interaction between the inert gas atoms and the attractive interaction coming from the reduced valence-electron density by interstitial inert gas atoms. Compared to He, the much greater attraction between the Ne/Ar atoms and the lower trigger condition of 'self-trapping process' for Ne/Ar clusters provide a reasonable explanation for the difference of irradiation effects on tungsten between He and Ne/Ar plasmas, i.e. Ne/Ar plasmas cannot result in the formation of holes/bubbles and fiber-form nanostructures on tungsten surface under the same irradiation conditions as He plasma.